Optimization of Land Services Through Adoption of Electronic Land Certificates - Oktavianto, Ridho; Riyanto, Taufan Fajar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The legal certainty of electronic land certificates in order to optimize land services. 2) The impact of the adoption of electronic land certificates on the security of data related to land ownership. This type of research is included in the scope of normative legal research. The approach method in this study is the statute approach. The types and sources of data in this study are secondary data obtained through literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) The legal certainty of electronic land certificates in order to optimize land services plays an important role in efforts to optimize land services in Indonesia. Electronic land certificates, which have been regulated through various regulations such as the Regulation of the Minister of ATR/BPN Number 3 of 2023 and supported by provisions in the ITE Law and the Job Creation Law, provide a guarantee of legality and legal validity that is equivalent to conventional land certificates. This ensures that transactions or disputes involving electronic documents can be recognized and resolved legally. 2). The impact of the adoption of electronic land certificates on the security of data related to land ownership, namely from the positive side, the technology used, such as encryption and digital signatures, ensures the integrity and confidentiality of land data. This electronic system allows for centralized storage that reduces the risk of physical data loss due to damage or disaster. In addition, the verification process becomes more efficient and accurate, reducing the potential for disputes related to land ownership. However, this adoption also presents challenges, such as the threat of hacking that requires high-level cybersecurity, dependence on reliable technological infrastructure, and the need to educate the public to understand and utilize this system properly. By strengthening the security system and increasing public awareness, electronic land certificates can improve the efficiency of land services while providing better legal protection for community land rights.Keywords: Certificate; Electronic; Optimization.